2023
DOI: 10.1093/ofid/ofad028
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Use of Bezlotoxumab and Fecal Microbiota Transplantation for the Treatment of Clostridioides difficile Infection

Abstract: Background We aimed to describe the frequency of use and effectiveness of bezlotoxumab (BZX) and fecal microbiota transplantation (FMT) in patients with Clostridioides difficile infection (CDI) in real-world practice. Methods Retrospective study conducted in a university hospital in which adult patients treated with BZX or FMT from January-2018 to April-2021 were included. The primary objective was to evaluate the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Sensitivity fidaxomicin use as the subsequent antibiotic treatment was assumed to be constant over 3 years after FMBL introduction, and assumptions on the projected market uptake of FMBL are yet to be tested when more data from the real world become available. Lastly, treatments that are not approved by the FDA or have limited use in real-world practice (e.g., fecal microbiota transplant [FMT], bezlotoxumab) were not considered in our study [6,32]. FMT is not FDA approved for rCDI prevention while bezlotoxumab is indicated for use in conjunction with antibiotic therapy to reduce rCDI, rather than after antibiotic therapy, and for patients with congestive heart failure, bezlotoxumab can only be used when benefit outweighs the risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity fidaxomicin use as the subsequent antibiotic treatment was assumed to be constant over 3 years after FMBL introduction, and assumptions on the projected market uptake of FMBL are yet to be tested when more data from the real world become available. Lastly, treatments that are not approved by the FDA or have limited use in real-world practice (e.g., fecal microbiota transplant [FMT], bezlotoxumab) were not considered in our study [6,32]. FMT is not FDA approved for rCDI prevention while bezlotoxumab is indicated for use in conjunction with antibiotic therapy to reduce rCDI, rather than after antibiotic therapy, and for patients with congestive heart failure, bezlotoxumab can only be used when benefit outweighs the risks.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments have limited use in realworld practice. For example, a recent study found that only 8.5% of episodes were treated using bezlotoxumab or FMT, and bezlotoxumab was used mostly in immunosuppressed patients [32]. It is anticipated that other FDA-approved rCDI treatments will become available in future years, and the budget impact model of FMBL suspension will need to be revisited when these new live biotherapeutic products become available.…”
Section: Discussionmentioning
confidence: 99%
“…To fully understand the clinical and economic values of FMBL in clinical practice, we evaluated the cost-effectiveness of FMBL compared to SOC from a US third-party payer perspective among patients with at least one recurrence. Other treatments (e.g., fecal microbiota transplant [FMT], bezlotoxumab) that are not FDA-approved or have limited use in real-world practice were not considered in our analysis [3,35]. FMT is not approved by the FDA for the prevention of rCDI while bezlotoxumab is indicated for use in conjunction with antibiotic therapy to reduce rCDI, rather than after antibiotic therapy, and for patients with congestive heart failure, bezlotoxumab can only be used when benefit outweighs the risks.…”
Section: Discussionmentioning
confidence: 99%
“…FMT is not approved by the FDA for the prevention of rCDI while bezlotoxumab is indicated for use in conjunction with antibiotic therapy to reduce rCDI, rather than after antibiotic therapy, and for patients with congestive heart failure, bezlotoxumab can only be used when benefit outweighs the risks. Further, recent real-world studies revealed that FMT and bezlotoxumab were used infrequently (only 8.5% of episodes were treated with bezlotoxumab or FMT for preventing rCDI) and bezlotoxumab was used mostly in immunosuppressed patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Two studies were randomized trials (MODIFY I and II) 6 and the remaining were observational. [11][12][13][14][15][16][30][31][32][33][34] Overall, 1472 patients received BEZ (691 excluding RCTs). Of the constituent studies, 5 studies, including 1734 patients, compared BEZ versus control (Table 1).…”
Section: Included Studies and Baseline Characteristicsmentioning
confidence: 99%